Constructing and Validating A Contextual Grit Scale for University Students in Indonesia: A Psychometric Study - Muhamad Syamsul Hayat; Rika Dwi Agustiningsih; Novita Sari (Proceedings International Conference on Education Innovation and Social Science, 2025)
This study aims to develop and evaluate the psychometric properties of a grit measurement instrument for university students in Indonesia, with a specific focus on the Bandung region. The theoretical framework conceptualized grit as comprising two core dimensions: perseverance of effort and consistency of interest. Thirty-two items were initially developed based on seven behavioral indicators and evaluated through expert judgment, language clarity tests, and item discrimination analysis. After a series of empirical tests involving 100 students for the tryout, 200 for the field test, and 40 for the test-retest, 14 items were retained based on reliability and validity criteria. Confirmatory Factor Analysis (CFA) supported the two-dimensional model with acceptable goodness-of-fit indices (RMSEA = 0.032, CFI = 0.977, TLI = 0.964, SRMR = 0.044). Internal consistency reliability was satisfactory (Cronbach's α = 0.790), and test- retest results demonstrated high temporal stability (r = 0.953, p < .001). These findings indicate that the developed grit scale is a valid and reliable instrument for assessing grit among Indonesian university students and can be applied in educational psychology research and interventions.